Ingestão de proteína e composição corporal em pacientes com doença de Parkinson leve a moderada - Monteiro, Pauliana Alencar (2023)
Introduction: Adequate protein intake throughout the aging process is important for maintaining muscle mass. Reduction in the quality and quantity of muscle mass and strength is characterized by sarcopenia. Nutritional disorders and changes in body composition are common symptoms in Parkinson's disease (PD). Goal: To evaluate protein intake and body composition in patients with mild to moderate Parkinson's disease in a Brazilian public tertiary hospital. Methodology: This is a cross-sectional study, observational, analytical, with quantitative approach, developed with patients of both sexes with mild to moderate PD (Hoehn & Yahr 1 to 3), aged ≥ 50 years and able to stand and walk without assistance, served between March 2021 and December 2022. Demographic data were collected, anthropometric, clinical and nutritional. The patients handgrip strength was assessed using the Sayehan dynamometer, as well as physical performance through the Short Physical Performance Battery (SPPB) and muscle mass through dual energy x-ray emission densitometry (DEXA) and Bioelectrical Impedance (BIA). Results: The study population comprised a total of 117 patients, of which 48 (41%) are women. The mean age was 66 ± 11 years and the mean disease duration was 10 ± 6 years. Furthermore, 10% (n=12) confirmed sarcopenia, the average Relative Skeletal Muscle Index (RSMI) was 7.27 ± 1.23kg/m². The average protein intake was 1.19 ± 0.41 g/kg. We found forty-one (35%) patients with low protein intake, defined as below 1g/kg/day, being the majority female. Positive screening for sarcopenia and higher fat mass index were independently associated with low protein intake. Appendicular skeletal muscle mass index showed a statistically significant direct correlation with protein intake (rho 0.29; p 0.002). Conclusion: The present study found a significant prevalence of low protein intake among PD patients in the mild to moderate stages of the disease. Low protein intake was independently associated with positive sarcopenia screening using the SARC-F, reduced lean appendicular mass and a higher fat mass index.